2014
DOI: 10.1021/jm500033r
|View full text |Cite
|
Sign up to set email alerts
|

Second Generation Steroidal 4-Aminoquinolines Are Potent, Dual-Target Inhibitors of the Botulinum Neurotoxin Serotype A Metalloprotease and P. falciparum Malaria

Abstract: Significantly more potent second generation 4-amino-7-chloroquinoline (4,7-ACQ) based inhibitors of the botulinum neurotoxin serotype A (BoNT/A) light chain were synthesized. Introducing an amino group at the C(3) position of the cholate component markedly increased potency (IC50 values for such derivatives ranged from 0.81 to 2.27 μM). Two additional subclasses were prepared: bis(steroidal)-4,7-ACQ derivatives and bis(4,7-ACQ)cholate derivatives; both classes provided inhibitors with nanomolar-range potencies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 79 publications
1
37
0
Order By: Relevance
“…Recently, Idenovi et al [106] reported a new class of hybrid molecule (CQ-Cholic acid derivatives, 41a and b, Figure 31) which was originally intended to develop as Botulinum neurotoxin inhibitors [106][107][108], but further study indicated that they are better inhibitors of malarial parasite too [106]. The hybrid compounds showed better activity profile on some strains than the standard drugs CQ, artemisnin and MFQ.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Recently, Idenovi et al [106] reported a new class of hybrid molecule (CQ-Cholic acid derivatives, 41a and b, Figure 31) which was originally intended to develop as Botulinum neurotoxin inhibitors [106][107][108], but further study indicated that they are better inhibitors of malarial parasite too [106]. The hybrid compounds showed better activity profile on some strains than the standard drugs CQ, artemisnin and MFQ.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…2331 Zinc-chelating molecules have been shown to be privileged inhibitor scaffolds against zinc metalloproteases e.g. matrix metalloproteinases (MMPs); 3234 for this reason, hydroxamates have been intensely studied as BoNT/A inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…IR (ATR): 3267w, 3060w, 3021w, 2917w, 2852w, 1609m, 1579s, 1531m, 1473w, 1449m, 1368w, 1329m, 1278w, 1241w, 1201w, 1167w, 1137w, 1118w, 1080w, 1040w, 876m, 800s cm À1 . 1 (18). 2-Formyl-5-(4 0 -methylphenyl)thiophene (100 mg, 0.49 mmol) and ACQ3 (173 mg, 0.74 mmol) were coupled to afford 18 (120.5 mg, 58%) using AcOH (42 lL, 0.74 mmol) and NaBH 4 (111 mg, 2.94 mmol).…”
Section: Chemistrymentioning
confidence: 99%
“…strains. 15,16 Our own research in the field of antimalarial ACQs afforded adamantane- 17 and steroidal-derived compounds, 18 2 and 3, respectively, as well as simple aminoquinolines bound to a single aromatic ring 4a and 4b, 19 Figure 1.…”
Section: Introductionmentioning
confidence: 99%